2010
DOI: 10.1002/jmri.22412
|View full text |Cite
|
Sign up to set email alerts
|

T1‐weighted ultrashort echo time method for positive contrast imaging of magnetic nanoparticles and cancer cells bound with the targeted nanoparticles

Abstract: Purpose To obtain positive contrast based on T1 weighting from magnetic iron oxide nanoparticle (IONP) using ultrashort echo time (UTE) imaging and investigate quantitative relationship between positive contrast and the core size and concentration of IONPs. Materials and Methods Solutions of IONPs with different core sizes and concentrations were prepared. T1 and T2 relaxation times of IONPs were measured using the inversion recovery turbo spin echo (TSE) and multi-echo spin echo sequences at 3 Tesla. T1-wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 27 publications
3
47
0
Order By: Relevance
“…The authors suggested that combining ultrashort T 2 * relaxometry with the multiple gradient echo T 2 * mapping techniques should improve the ability to measure the relaxation of tissues with high densities of implanted iron-labeled cells. In another investigation, T1-weighted positive contrast enhancement from SPIO particles was achieved from the UTE imaging then this sequence, taking advantage of the unique effect of MNPs on relaxation time domain, was also examined to validate its positive contrast imaging capability of "probe" targeting to U87MG human glioblastoma cells through an SPIO conjugated RDG with high affinity to the cells overexpressing integrin v 3 (Zhang, 2011). So the study was regarded as providing a dual contrast imaging method from UTE technique plus T 2 -weighted TSE images in its application of molecular imaging of glioma with potential quantification of SPIO nanoparticles suggested by previously published report ).…”
Section: Ultra Short Echo Time Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that combining ultrashort T 2 * relaxometry with the multiple gradient echo T 2 * mapping techniques should improve the ability to measure the relaxation of tissues with high densities of implanted iron-labeled cells. In another investigation, T1-weighted positive contrast enhancement from SPIO particles was achieved from the UTE imaging then this sequence, taking advantage of the unique effect of MNPs on relaxation time domain, was also examined to validate its positive contrast imaging capability of "probe" targeting to U87MG human glioblastoma cells through an SPIO conjugated RDG with high affinity to the cells overexpressing integrin v 3 (Zhang, 2011). So the study was regarded as providing a dual contrast imaging method from UTE technique plus T 2 -weighted TSE images in its application of molecular imaging of glioma with potential quantification of SPIO nanoparticles suggested by previously published report ).…”
Section: Ultra Short Echo Time Methodsmentioning
confidence: 99%
“…The more recent investigation (Zhang, 2011) demonstrated that an appropriate SPIO core size and concentration range was paid much attention to obtain positive contrast with UTE imaging, and this technique could be used with the receptor targeted SPIO molecular imaging probe so as to provide an opportunity for monitoring cancer cells with overexpression of integrin v 3 in addition to negative contrast by the approach of T 2 relaxometry mapping.…”
Section: T 1 and T 2 (T 2 *) Multi-contrast For Cell Trackingmentioning
confidence: 99%
“…The images reflect both tissue MIOP concentration and deviations of the local magnetic field produced by the particles [50][51][52][53][54]. Techniques using SWIFT [55] and UTE [56][57][58] have also been successful for imaging MIOPs.…”
Section: Positive Contrast and White Marker Imagingmentioning
confidence: 99%
“…Contrast enhancement with gadolinium chelates may be seen within previously invisible tissues using UTE sequences [128], as well as with MIOPs [50][51][52][53][54][55][56][57][58]. Dental imaging has successfully identified caries [129][130][131].…”
Section: Other Proton Applicationsmentioning
confidence: 99%
“…5 Maximum advantage of iron-based nanoparticles for imaging has been taken in special methods for MRI such as ultrashort echo time imaging, which improves nanoparticle contrast and enables iron quantification in tissues. 6 Magnetic nanoparticles have also been investigated for cancer therapy application, as they are suitable for magnetic hyperthermia. 7,8 Magnetic nanoparticles may also be designed for multiple potential therapeutic approaches as chemotherapeutics delivery carriers and photodynamic therapy.…”
Section: Introductionmentioning
confidence: 99%